IMF Research Bulletin, December 2013. (IMF Research Bulletin; IMF Research Bulletin, 2013)
In the December 2013 IMF Research Bulletin, the Research Summaries look at 'Reforming Dual Labor Markets in Advanced Economies' (Giovanni Ganelli) and 'Rating Through-The-Cycle: What Does the Concept Imply for Rating Stability Accuracy' (John Kiff, Michael Kisser, and Liliana Schumacher). The Q and A discusses Seven Questions on Financial Crises (Stijn Claessens, M. Ayhan Kose, Luc Laeven, and Fabian Valencia). This issue also includes a listing of recent IMF Working Papers and IMF Staff Discussion Notes, as well as Recommended Readings from the IMF Bookstore. The top-viewed articles from recent of issues of 'IMF Economic Review' are featured.